The The Development of M.Vocset for Building Prescholers English Vocabulary Inventory - Dania Piolita (Universitas Sarjanawiyata Tamansiswa, 2021)
The objectives of this research are (1) to develop M-Vocset for teaching English for young learner and (2) to know the benefit of M-Vocset for teaching English in Kangaroo Preschool. In this research, researcher used Research and Development (R&D) model from Borg and Gall. To simplify this research, the researcher shortened it to four stages that are: data collection and information, planning, product development and final product. Data collection technique used in this research is interview and document analysis. This research was conducted at Kangaroo Preschool with age 2-4 years old. The findings of this research are: analysis needs of students and document analysis. The result is that researcher use Holy days Â as learning material to be developed. To accomplish M-Vocset, the researcher asked for input from the expert team and also the teacher there. Regarding the benefits, it is easy to use and it is to teach students how to write a sentence in English. M-Vocset develops student character regarding tolerance.